2015
DOI: 10.1371/journal.pone.0116397
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Soil Cadmium on Land Snails: A Two-Stage Exposure Approach under Semi-Field Conditions Using Bioaccumulative and Conchological End-Points of Exposure

Abstract: Land snails are highly tolerant to cadmium exposure and are able to accumulate soil cadmium independently of food ingestion. However, little information exists on the kinetics of cadmium retention in terrestrial gastropods exposed to an increase in the soil cadmium content, over time. There is also little knowledge about how exposure to cadmium-polluted soils influences shell growth and architecture. In this context, we examined cadmium accumulation in the hepatopancreas and shell of juvenile Cantareus aspersu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
3
7
0
Order By: Relevance
“…aspersus , concentrated substantive amounts of cadmium in the hepatopancreas without significant lethal effects. This is in accordance with the results of other investigations [ 13 , 34 ], confirming the exceptional tolerance of this gastropod species to Cd exposure [ 13 , 16 , 34 , 35 , 52 , 53 ]. Most studies to date found no significant mortality in C .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…aspersus , concentrated substantive amounts of cadmium in the hepatopancreas without significant lethal effects. This is in accordance with the results of other investigations [ 13 , 34 ], confirming the exceptional tolerance of this gastropod species to Cd exposure [ 13 , 16 , 34 , 35 , 52 , 53 ]. Most studies to date found no significant mortality in C .…”
Section: Discussionsupporting
confidence: 93%
“…There is also compelling evidence for the presence of 5mC in the genome of the land snail Helix pomatia (Linnaeus, 1758) [ 11 ]. However,there is no relevant epigenetic information available concerning other terrestrial gastropods that are commonly used as ecotoxicological study systems, such as the brown garden snail Cantareus aspersus (Müller, 1774)[ 12 16 ]or the grove snail Cepaea nemoralis (Linnaeus, 1758)[ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium sulfate will extend our knowledge on the bioavailability of different chemical forms of Cd in land snails, which is currently limited to cadmium chloride (Coeurdassier et al, 2002;Nica et al, 2015;Nica et al, 2017aNica et al, , 2017b and cadmium nitrate (Laskowski and Hopkin, 1996).…”
Section: Breeding Methodsmentioning
confidence: 99%
“…These invertebrates serve as excellent macro-concentrators for cadmium (Dallinger and Rainbow, 1993), with the hepatopancreas being the main retention endpoint (Russel et al, 1981;Rabitsch, 1996;Dallinger et al, 2004;Fritsch et al, 2011;Pauget et al, 2013). Therefore, the concentration of Cd in this organ is a reliable tool for exposure assessment and provides accurate estimates of its bioavailability for these mollusks (Rabitsch, 1996;Nica et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Biomarker evaluation. Test specimens were measured with a Vernier caliper and weighed in analytical balance with a sensitivity of 0.1 g. Organisms were euthanized by fast-freezing them at -20 °C/30 min, as previously reported (Nica et al, 2015). Tissues of tegogolo (foot, head, intestine, mantle, digestive gland, and kidney) were obtained according to the anatomy of gastropods (Barnes, 1980).…”
Section: Methodsmentioning
confidence: 99%